MIKROBA ENDOFIT DARI TANAMAN SRIKAYA (Annona squamosa L.) SEBAGAI PENGHASIL ANTIMIKROBA Staphylococcus aureus DAN Candida albicans - Ruth Melliawati; Sunifah Sunifah (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Various studies indicated that endophytic microbes lived in the plant tissues and produced antimicrobial compounds. Sugar-apple plant (Annona squamosa L) contained alkaloids, cyanogenic glycosides, and flavonoids. The purpose of this reasearch were (1) to determine the endophytic microbes isolated from sugar-apple plant (2) to study inhibiting capabillity of endophytic isolate against Staphylococcus aureus and Candida albicans, (3) to analyze antimicrobial compounds produced by the potential endophytic isolate. Diffusion agar plate methode was used to assessed antimicrobial activity. Antimicrobial compounds were analyzed by Thin Layer Chormatography (TLC) and High Performance Liquid Chormatography (HPLC), compared with erythromycin, metronidazole and tetracycline. Twelve bacterial isolates and 24 fungus were isolated. Selected bacteria, BMC 1.1, showed the biggest clear zone on C. albicans culture on agar medium, meanwhile selected fungi, BTCK 1.1T, formed the biggest colony on S. aureus culture on agar medium. TLC and HPLC analysis showed that the Rf value of BMC 1.1 and BTCK 1.1T chloroform phase fractions was similiar to metronidazole. Metronidazole concentration in C1, C2, Ck1 and Ck2 fraction were 170.98 ppm, 18.27 ppm, 1.51 ppm and 4.14 ppm respectively.